Pelatihan Penggunaan Media Pembelajaran Daring di MTs Sirajul Huda - Adipta, Marazaenal; Suandi, Suandi; Muzakir, Muzakir; Sahabudin, Sahabudin; Mawarzani, Sapka; Sanwani, Sanwani; Masnun, Masnun; Idham, Idham; Dasarja, Lalu Butsiawan; Busrono, Lalu Muhammad (UKInstitute, 2022)
The passing of the covid-19 pandemic leaves a variety of new habits implemented by schools, especially teachers in the learning process. The new habit in question is that teachers use online media to carry out the learning process. This is also a form of demand from the government to reduce the spread of the COVID-19 pandemic. This training activity on the use of online learning media begins with a theoretical explanation of the definition of online learning and the various online learning media platforms currently available. Of course, as educators must be able to choose the right online learning media so that students also do not experience obstacles and difficulties in following the learning delivered by the teacher. Before entering the training stage, the speaker provided material about learning media in general and the difference between online learning media. On this occasion, what was conveyed was about google classroom, zoom meeting and google form. Program socialization was carried out to introduce the program and how to use it to all teachers at MTs Sirajul Huda. Abstrak: Berlalunya pandemi covid-19 menyisakan berbagai kebiasaan-kebiasaan baru yang diterapkan oleh pihak sekolah terutama guru dalam proses pembelajaran. Kebiasaan baru yang dimaksud adalah guru menggunakan media online untuk melaksanakan proses pembelajaran. Hal tersebut juga sebagai bentuk tuntutan dari pemerintah untuk mengurangi penyebaran pandemi covid-19.Kegiatan pelatihan penggunaan media pembelajaran online ini diawali dengan penjelasan secara teoritis mengenai definisi pembelajaran online dan berbagai macam platform media pembelajaran online yang ada saat ini. Tentu sebagai pendidik harus dapat memilih media pembelajaran online yang tepat agar siswa juga tidak mengalami kendala dan kesulitan dalam mengikuti pembelajaran yang disampaikan oleh gurunya. Sebelum masuk ke tahap pelatihan, pembicara memberikan materi tentang media pembelajaran secara umum dan perbedaannya dengan media pembelajaran online. Dalam kesempatan ini yang disampaikan adalah tentang google classroom, zoom metting dan google form. Sosialisasi program dilakukan untuk mengenalkan program serta cara penggunaannya kepada semua guru yang ada di MTs Sirajul Huda.